1992
DOI: 10.1007/bf02171052
|View full text |Cite
|
Sign up to set email alerts
|

Chinese medicine, Coix seeds increase peripheral cytotoxic T and NK cells

Abstract: Coix seeds, a Chinese medicine have been used in Japan and reported to be effective in patients with verruca vulgaris and verrucae planae juveniles. We investigated the in vivo effects on lymphocyte subsets in seven healthy volunteers who took six tablets of Coix seeds three times a day (a typical dose) for four weeks. Leukocyte counts and the percentage of total lymphocytes did not change but the percentages of CD3+CD56+ cells and CD16+CD57- cells increased significantly. These results indicate that Coix seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Park et al found that lipid components in plasma and feces decreased in rats fed different fat cholesterol diet with adlay seed (Park et al, 1988). Hidaka et al demonstrated that ingestion of adlay seed tablets could increase the activities of cytotoxic T-lymphocytes and natural killer cells (Hidaka et al, 1992). Check and K'Ombut also found decreased fibrinolytic activities of blood plasma of Wistar rats fed an adlay mixed diet (Check and K'Ombut, 1995).…”
Section: Introductionmentioning
confidence: 94%
“…Park et al found that lipid components in plasma and feces decreased in rats fed different fat cholesterol diet with adlay seed (Park et al, 1988). Hidaka et al demonstrated that ingestion of adlay seed tablets could increase the activities of cytotoxic T-lymphocytes and natural killer cells (Hidaka et al, 1992). Check and K'Ombut also found decreased fibrinolytic activities of blood plasma of Wistar rats fed an adlay mixed diet (Check and K'Ombut, 1995).…”
Section: Introductionmentioning
confidence: 94%
“…Adlay is mainly planted in China and Japan, where it is considered a health food supplement (Lee, Lin, Cheng, Chiang, & Kuo, 2008). Many recent studies have indicated that the consumption of adlay seed is beneficial to human health (Hidaka, Kaneda, Amino, & Miyai, 1992;Hsu, Lin, Lin, Kuo, & Chiang, 2003). In addition, adlay extract exhibits antiinflammatory (Nagao, Otsuka, Kohda, Sato, & Yamasaki, 1985), hypoglycemic (Takahashi, Konno, & Hikino, 1986) and anti-tumor effects (Chang, Huang, & Hung, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Adlay has been reported to have various immunomodulatory activities, such as anti-complementary, anti-inflammatory and anti-allergic effects (Takahashi et al, 1986;Otsuka et al, 1988;Seo et al, 2000;Hsu et al, 2003;Chen et al, 2010). Moreover, the consumption of adlay extracts can increase the activities of cytotoxic T cells and natural killer (NK) cells (Hidaka et al, 1992). The methanolic extract of adlay seeds inhibits NO and O 2 −• production by activated macrophages (Seo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%